Comparative analysis of machine learning models for stock price analysis across different dataset sizes - Srabon, Abir Alam; Abrar, Mahmudul Hasan; Rahman, Nimur; Ahmed, Washif Uddin; Hridy, Salamat Sajid (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.